2003
DOI: 10.1080/09603100110117866
|View full text |Cite
|
Sign up to set email alerts
|

Credit channel and credit shocks in Canadian macrodynamics - a structural VAR approach

Abstract: The idea that financial structure and output determination may be interrelated has gone through several cycles over the past half a century since its inception at the time of the Great Depression. In its latest reincarnation as the theory of financial acceleration, it considers financial factors as propagation mechanisms for the disturbances originating in the real economy. The agency costs of credit allocation by the financial intermediaries play a central role in this theory. Financial factors have rarely be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
(24 reference statements)
1
9
0
1
Order By: Relevance
“…That is, our results suggest that consumers are more likely than firms to be constrained during a monetary downturn. The conclusion that consumers, not businesses, are credit constrained is consistent with the results of Safaei and Cameron (2003) 20 . Although the theoretical literature on agency costs in financing has typically focused on loans to firms, there are now several papers that build dynamic business cycle models in which frictions associated with lending to consumers play a crucial role (see, e.g., Campbell and Hercowitz 2004; Iacoviello 2005).…”
Section: Concluding Commentssupporting
confidence: 82%
See 1 more Smart Citation
“…That is, our results suggest that consumers are more likely than firms to be constrained during a monetary downturn. The conclusion that consumers, not businesses, are credit constrained is consistent with the results of Safaei and Cameron (2003) 20 . Although the theoretical literature on agency costs in financing has typically focused on loans to firms, there are now several papers that build dynamic business cycle models in which frictions associated with lending to consumers play a crucial role (see, e.g., Campbell and Hercowitz 2004; Iacoviello 2005).…”
Section: Concluding Commentssupporting
confidence: 82%
“…The latter is consistent with the pattern we find during a monetary downturn. Note that while we do not separately identify a credit supply shock–which requires a complex set of restrictions–it is possible that our monetary policy shock captures, in part, a credit supply shock like the one identified in Safaei and Cameron (2003).…”
mentioning
confidence: 99%
“…This in turn will quickly increase the aggregate demand. A similar assumption is used by Safaei and Cameron (2003) and Berkelmans (2005) in the case of Canada and Australia respectively.…”
Section: (A) the Structural Modelmentioning
confidence: 88%
“…The identification of banking channels responsible for real effects revealed that credit channel was active in Canada, Finland, the UK, and in the euro area. In turn, the balance sheet channel was found important in the US and Germany (Chrystal and Mizen, 2002;Safaei and Cameron, 2003;Lown and Morgan, 2006;Iacoviello and Minetti, 2008;Tamási and Világi, 2011;Musso et al, 2011;Ciccarelli et al, 2015).…”
Section: Section 1 Dependence Between Banking and Real Sectorsmentioning
confidence: 99%